Pendidikan Kesehatan Reproduksi Untuk Penurunan Perilaku Seksual Pranikah pada Remaja - Sri Helmi Hayati; Rahma Widyana; Santi Esterlita Purnamasari (LPPM Universitas Proklamasi 45, 2021)
This research aims to examine the effect of reproduction health education toward the reduction of premarital sexual behavior on adolescents. The research subjects were 34 subjects who were assigned into 2 groups; 17 subjects were experimental group while 17 subjects were there control group. The research design use the pretest-postest control group design. The data analysis use the U Mann Whitney to examine the score difference in the experimental and the control group and the Wilcoxon Rank Test to examine the score difference in the experimental group before and after treatment. Based on the data analysis by the U Mann Whitney, it is found that there is different level of premarital sexual behavior on the group which was exposed to the reproduction health education committed to the group that was not exposed proven by Z = -3.089 p = 0.002 (p<0.05).The premarital sexual behavior on the group which had the reproduction health education is lower than group are not given reproduction health education. The analysis by the Wilcoxon Rank Test found that there is different score in the premarital sexual behavior in the experimental group after it was given the reproduction health education proven by the score Z = -3.219 p = 0.001<0.05. This result indicates that there is significant difference in the premarital sexual behavior on the subjects before and after the reproduction health education was given. The level of premarital sexual behavior after given reproduction health education is lower compared to before given reproduction health education.